Seroprevalence of Hepatitis B Among Healthcare Workers in Asia and Africa and Its Association With Their Knowledge and Awareness: A Systematic Review and Meta-Analysis - Maamor, Nur Hasnah; Muhamad, Nor Asiah; Mohd Dali, Nor Soleha; Abdul Mutalip, Mohd Hatta; Leman, Fatin Norhasny; Aris, Tahir; Lai, Nai Ming; Abu Hassan, Muhammad Radzi (Frontiers in Public Health, 2022)
Introduction The hepatitis B virus (HBV) is a blood-borne virus that can be transmitted by percutaneous and mucocutaneous contact with infected bodily fluid. Healthcare workers (HCWs) are more exposed to HBV infection. They must have a thorough understanding of HBV infection since they can contract and spread the virus. In this study, we systematically reviewed all published evidence on the seroprevalence of Hepatitis B virus (HBV) infection among HCWs. and synthesize evidence on the association between knowledge and awareness with HBV infection. Methods We searched PubMed, EMBASE, Cochrane Library and Scopus for studies reporting on HBV seroprevalence from January 1997 to September 2021 among healthcare workers. We used random-effects meta-analyses to estimate the pool prevalence of HBV infection. Results We identified 25 studies that met our inclusion criteria, with data on 10,043 adults from 11 countries and two regions: Africa and Asia. The overall seroprevalence of HBV was 5.0% (95% confidence interval [CI] 3.6%), with Africa reporting higher estimates (5.0%, 95% CI 3.7%) than Asia population (4.0%, 95% CI 1.9%). The highest pooled prevalence estimate in African countries came from studies published in the Cameroon region (8.0%, 95% CI 5–10%) while the lowest came from Ethiopia (4.0%, 95% CI 2.6%). The overall seroprevalence estimates in the African population were significantly higher than those in the Asian group. Studies in Africa found that the average knowledge and seroprevalence were 1.4% and 11.0%, respectively where, eight studies (53.3%) reported good knowledge and seven studies (46.7%) reported average knowledge. In Asia, two studies (40.0%) reported good knowledge, one study (20.0%) reporting average knowledge, and two studies (40.0%) reporting poor knowledge. African studies demonstrated good knowledge despite the fact that their HBV infection rate was higher than 6.7%. Conclusion Africa and Asia have the highest seroprevalence of HBV infection. Improving the comparability of epidemiological and clinical studies constitutes an important step forward. More high-quality data is needed to improve the precision of burden estimates. Systematic Review Registration PROSPERO CRD42021279905.